Role of antioxidants in the treatment of oral submucous fibrosis: A clinical and histopathological study - B Vijay Kumar (Wolters Kluwer Medknow Publications, 2009)
Background: With the increased incidence of oral submucous fibrosis and treatment being not completely satisfactory, the need for alternative method of treatment is increasing. The present study evaluates the efficacy of oral antioxidant preparations in the treatment of clinically and histopathologically proved oral submucous fibrosis. Methods: Study was conducted in 40 patients of two groups of all ages who were clinically and histopathologically proved with oral submucous fibrosis with standard data grading and biopsies before and after the study for evaluation. Results: On comparison with the control group of placebo treatment, antioxidant therapy has shown a significant improvement (i e 70'0 P < 0.001 for interincisal distance: P < 0.001 for tongue protrusion and P < 0.05 for blowing capacity) and moderate improvement in histopathological findings of the treatment group. Conclusions: Significant number of cases have shown increased mouth opening, tongue protrusion. and blowing capacity and decreased burning sensation after treatment with antioxidants. Histopathologically, there is a certain amount of improvement, but not proportional with clinical improvement which shows that antioxidants can be useful therapeutic adjuvants to the already available treatment modalities in oral submucous fibrosis.